Repertoire Construction for Critical Cross-Cultural Literacy of English Majors: Based on the Research Paradigm of Systemic Functional Linguistics - Zhao, Ran; Lu, Danyun (Frontiers in Psychology, 2022)
The ambiguous development trend of cultural globalization brings both opportunities and challenges to China’s cultural development. English major in colleges and universities, a discipline of cross-cultural education, should look at the cultural communication of the target country dialectically based on the national consciousness of the home country. Since the end of the 20th century, administrators and scholars have paid attention to critical thinking, critical cultural awareness, and critical skills in cross-cultural communication, which are important components of the cross-cultural meaning system. Therefore, all these are collectively referred to as critical cross-cultural literacy (CCCL). On the basis of the research paradigm of systemic functional linguistics (SFL), a language is a semiotic system that creates meaning. Thus, to help students construct and improve their individual CCCL repertoire, teachers need to guide them to critically study and analyze the discourse purpose of the textbook author as well as their language methods and strategies to enrich their meaning potential.